ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI MASYARAKAT DI PROVINSI ACEH - Tarmizi Gadeng (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
The main objective of this study is to find out the impact of the inflation rate,percapita income as wall as the interest rate on the household comsumption of the population of Aceh.Secondary data 1983 – 2008 are collected or couning from various ageucig and instution and ordinary least square econometric model used as a method of analysis.            The result of the study tells us that the rate of inflation and the percapita income hare positive and significoutly effect on the household consumtion while the rate of interest on the other hand statistically has a negative and not significant effect on the house hold consumption. The interest rate which reflect the influence of the consumption has a positive, not significantly and in elactic.